Pemberdayaan Ekonomi dan Pariwisata Masyarakat Kampung Singah Mulo sebagai Kampung Satelit di Kabupaten Gayo Lues - Sutrisno Sutrisno; Mina Semayang; Diky Prasetyo; Hasni Rizki; Siti Haji; Linda Mahara; Diki Firmansyah (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2023)
Singah Mulo is a village located in Putri Betung District, Gayo Lues Regency, Aceh Province. Singah Mulo Village is located on the Blang Kejeren-Kutacane road and is a strategic area and satellite that connects the provinces of Aceh and North Sumatra. Kampung Singah Mulo has economic potential and natural tourism which is the flagship of Putri Betong District, Gayo Lues Regency so that internal and external community empowerment needs to be carried out. This service method is carried out through Participatory Action Research where the community becomes a key actor in empowering the community's economy and developing tourism in Kampung Singah Mulo. The result of this service is that the people of Kampung Singah Mulo are assisted in making various snacks/snacks that are characteristic of Kampung Singah Mulo and assisting the community in managing Micro, Small and Medium Enterprises (UMKM). Then, community assistance in tourism development in the form of Kampung Singah Mulo hot springs in the form of management of tourist sites and digital tourism promotion.